2023
DOI: 10.1002/cphc.202200775
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Chemical State of Palladium in Operating In2O3 Gas Sensors: Metallic Pd Enhances Sensing Response and Intermetallic InxPdy Compound Blocks It

Abstract: The sensing response of metal oxides activated with noble metal nanoparticles is significantly influenced by changes to the chemical state of corresponding elements under operating conditions. Here, a PdO/rh-In 2 O 3 consisting of PdO nanoparticles loaded onto rhombohedral In 2 O 3 was studied as a gas sensor for H 2 gas (100-40000 ppm in an oxygen-free atmosphere) in the temperature range of 25-450 °C. The phase composition and chemical state of elements were examined by resistance measurements combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The data generated with both techniques can be combined to obtain a more thorough description of a catalyst in situ. This RMSI results in the formation of irreversible intermetallic compounds (IMCs) in the PdO/rh-In 2 O 3 system, influencing its catalytic and gassensing properties (Ovsianytskyi et al, 2023). Our previous in situ synchrotron PXRD studies showed that 5 wt% PdOloaded rh-In 2 O 3 undergoes a sequence of phase transformations upon heating under a pure H 2 atmosphere at 1 bar and up to 500 C (Ovsianytskyi et al, 2023;Schlicker et al, 2018b).…”
Section: Combined In Situ Pxrd and Xafs Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The data generated with both techniques can be combined to obtain a more thorough description of a catalyst in situ. This RMSI results in the formation of irreversible intermetallic compounds (IMCs) in the PdO/rh-In 2 O 3 system, influencing its catalytic and gassensing properties (Ovsianytskyi et al, 2023). Our previous in situ synchrotron PXRD studies showed that 5 wt% PdOloaded rh-In 2 O 3 undergoes a sequence of phase transformations upon heating under a pure H 2 atmosphere at 1 bar and up to 500 C (Ovsianytskyi et al, 2023;Schlicker et al, 2018b).…”
Section: Combined In Situ Pxrd and Xafs Studymentioning
confidence: 99%
“…This RMSI results in the formation of irreversible intermetallic compounds (IMCs) in the PdO/rh-In 2 O 3 system, influencing its catalytic and gassensing properties (Ovsianytskyi et al, 2023). Our previous in situ synchrotron PXRD studies showed that 5 wt% PdOloaded rh-In 2 O 3 undergoes a sequence of phase transformations upon heating under a pure H 2 atmosphere at 1 bar and up to 500 C (Ovsianytskyi et al, 2023;Schlicker et al, 2018b). In this experiment we studied the influence of H 2 on the sequence of these phase transformations.…”
Section: Combined In Situ Pxrd and Xafs Studymentioning
confidence: 99%